Fraud Prevention in Charities Using Blockchain System - Upadhyay, Astha; Suresh, Rahul; Kumar, K Senthil (International Journal of Psychosocial Rehabilitation, 2020)
The charity is a challenging forum for investment and requires immense brainstorming before one shall put their hard-earned money to a good cause. This project aims at reducing the fraud that takes place due to a hike in online transactions. This paper seeks to analyze the shortcomings of the current system and to build a model that would mitigate most of them by implementing more efficient algorithms. Using this model, anyone can monitor the charity work that they want to invest in; and maximize profit for thesociety.